Determination of Warehouse Locations for Logistics Services in an Integrated City Spatial System (Case Study in Bekasi City) - Budiyanto, Sigit; Prasetyo, Irwan; Zefri, Zefri (Universitas Islam Sultan Agung Semarang, 2024)
Human needs consisting of clothing, food, shelter and medicines will increase every year and require services. There are many planning changes in the digital era, so it is necessary to study the location theory of logistics service storage warehouses in the city spatial system. This study aims to identify the characteristics of existing logistics services, examine the determination of the location of existing logistics service storage warehouses and become an opportunity for logistics service players who wish to be located in the region. This study uses location theory for location determination, nearest Neighbour ratio analysis and analytical hierarchical process in determining the criteria and alternative locations for logistics service storage warehouses. The results of the analysis in the identification of characteristics, namely location, company operations, company management, settlement patterns affect the distribution pattern of logistics services. Then the more dominant criterion is the market with the value obtained (0.542) because in carrying out any business activity, you have to see who is the market for the business activities being carried out. At the location of the case study as a sample, namely Jatiraden (0.618) which has the most potential according to criteria related to market, cost, human resources, infrastructure and institutions. The conclusions obtained for operational matters using three-wheeled vehicles in the distribution of logistics services are an alternative in distributing uniform residential areas. More loads and easier mobility because the accessibility of vehicles in uniform residential patterns tends to be wide. Suggestions that can be conveyed in determining the location and making any business activity must be seen from the urban area planning. So that stakeholders can refer to the city's spatial planning system, so that policies made by the government can be compatible and aligned with logistics service companies.